The Effect of Propolis Product Price and Promotion on Consumer Purchase Interest at PT. Nano Herbaltama International in Setu District, South Tangerang City - Arman Syah; Dedek Kumara; Nefo Indra Nizar; Uswatun Hasanah (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
The purpose of this study was to determine the effect of price and promotion on consumer buying interest at PT Nano Herbaltama Internasional, either partially or simultaneously. The research method used is a quantitative method with a descriptive approach. The sampling technique used is a saturated sample using a sample of 113 respondents from the entire population. The results of the research have a significant effect on buying interest partially, as evidenced by the regression equation Y = 11.097 + 0.902X1, a correlation coefficient of 0.860 means that the two variables have a very strong relationship. The value of determination is 86%. The hypothesis test obtained a value tcount > ttable or (17.767 > 1.981) and strengthened by a significant value (0.000 <0.05). Promotion has a significant effect on consumer buying interest partially as evidenced by the results of the regression equation Y = 7.972 + 0.669X2, the correlation coefficient of 0.820 means that the two variables have a very strong relationship level. The value of determination is 82%. The hypothesis test obtained a value of tcount > ttable or (15.083> 1.981) and strengthened by the significance value (0.000 <0.05). The results of the research on price and promotion simultaneously have a significant effect on consumer buying interest as evidenced by the results of the regression equation Y = 7.661 + 0262X1 + 0.616X2. The value of the correlation coefficient between the independent variable and the dependent variable was obtained at 0.877, which means that it has a very strong relationship. The value of the coefficient of simultaneous determination is 87.7%. Simultaneous hypothesis testing obtained Fcount > Ftable or (182,776 > 2,690) and strengthened by the significance value (0.000 < 0.05). Thus H0 is rejected and H3 is accepted. This means that it can have a significant effect simultaneously between price and promotion of consumer buying interest.